A EDUCATORS CONTRIBUTION TO EMPLOYEE PERFORMANCE FOR LEARNING - WINANTI; DWI RIZQIANI INDRAWATI; EKA IMELIYANTI; Moh Nuril Anwar; Francisca Sestri Goetjahjanti; Tatang Imam Sadewa (International Journal of Innovation Research in Education, Technology and Management, 2026)
The purpose of this research is to obtain information about the efectiveness of school management in the place i work as an ASN PPPK educator who teaches the subject of geography using the 2013 curriculum or more known as kurtilas. This research started in may 2024. In the learning process teachers are seen as having an important role, especially in helping students to develop their potential in cognitive, affective and psychomotor abilities, teachers also strive to arouse curiosity, encourage independence and accuracy of intellectual logic, and create conditions for success in learning. Teacher performance can be seen and measured based on the competency specifications/criteria that each teacher must have. The educators who are the objects of the research are educatiors from senior high school 10 Tangerang district and the musyawarah of geography teachers in Tangerang district (MGMP Geography) from state secondary and secondary schools on the privatw one that is in Tangerang district. The method used in this research was a questionnaire method or data collection via the google form and whatsapp applications also a questionnaire which was share using a hardcopy specifically for educators at sma negeri 10 Tangerang district. This method was used to get the actual state his and research result described. Data collection techniques used through observation and documentation. The informants in this case are the teachers of Tangerang district 10 state high school and teachers who joined in the teacher’s for the geography subject of Tangerang district. In this conclusion it can be conclued that the effectiveness of school management will be good and orderly if educators are able to cooperate with each other and create a confortable atmosphere in the teacher’s room for fellow educators or other school citizens.